Effect Of Chicken Manure And Volcanic Ash On The Growth And Production Of Shallot (Allium ascalonicum L.) And P Availability In Paddy Field - Ernitha Panjaitan (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to determine the effect of applying chicken manure and volcanic ash on the growth and production of shallots (Allium ascalonicum L.) and P availability in paddy fields. This research was conducted in paddy field at Jln. Harmonika Baru Pasar II, Tanjung Sari Urban Village, Medan Selayang Sub-district, Medan with an altitude of ± 30 meters above sea level. This research was conducted from December 2019 to February 2020. This study used a Randomized Group Design (RAK) with 2 treatment factors. The first factor, chicken manure with 4 levels, namely: A0 = Control (without chicken manure), A1 = 3.75 kg/plot (10 tons/ha), A2 = 7.5 kg/plot (20 tons/ha) and A3 = 11.25 kg/plot (30 tons/ha). The second factor is volcanic ash with 4 levels, namely: V0 = Control (no volcanic ash), V1 = 1.88 kg/plot (5 tons/ha), V2 = 3.75 kg/plot (10 tons/ha) and V3 = 5.62 kg/plot (15 tons/ha). The results showed that the treatment of chicken manure doses up to a dose of 7.5 kg/plot significantly increased leaf length, number of bulbs, wet weight of bulbs/plant, wet weight of bulbs/plot, dry weight of bulbs/plant, dry weight of bulbs/plot, base saturation, C-Organic, soil pH, and soil P availability, but had no significant effect on soil CEC. The treatment of vulaknik ash dose had no significant effect on leaf length, number of tubers, wet weight of tubers/plant, wet weight of tubers/plot, dry weight of tubers/plant, dry weight of tubers/plot, soil CEC, base saturation, C-Organic, soil pH and P availability. The interaction between doses of chicken manure and volcanic ash had a significant effect on the wet weight of tubers/plot and dry weight of tubers/plot, but had no significant effect on leaf length, number of tubers, wet weight of tubers/plant, dry weight of tubers/plant, soil CEC, base saturation, C-Organic, soil pH and P availability.